GENERATION MEAN ANALYSIS FOR YIELD AND YIELD COMPONENTS IN SESAME (Sesamumindicum L.) - Ali, Khalafalla A. (International Journal of Environment, 2015)
Two parents with contrasting characters were used, viz; Gd2002SPSN.29 and Ziraa-9 described as (P1) and (P2) respectively. They were selected from the sesame breeding program, Gedarif Research Station, ARC, Sudan. In season 2004 the two parents were crossed to produce F1 hybrid. In season 2005 parents and their F1 were grown. Part of the F1 was selfed to produce F2 and the other part was back crossed to both parents to produce Bc1 and Bc2 progenies. In season 2006 the parents (P1, P2), and their F1and F2 and back crosses (Bc1, Bc2) populations were evaluated in a randomized complete block design with three replicates. A wide range of variability was exhibited for most of the characters. The highest seed yield was obtained by the BC2 (714 Kg.ha-1), while the lowest was obtained by the BC1 (286 Kg.ha-1). Considering the nature and magnitude of gene action, improvement of days to 50% flowering, days to maturity, plant height, number of branches plant-1, height to first branch, height to first capsule, capsule length and 1000-seed weight could be achieved through simple pedigree method while hybrid breeding would be most effective for seed yield plant-1 and seed yield.ha-1International Journal of Environment Volume-4, Issue-3, June-August 2015Page: 111-120